THE DEVELOPMENT OF MANAGEMENT MODEL ON COLLABORATIVE-BASED STUDENTS' SCIENTIFIC WRITING MENTORING THROUGH AN ONLINE RESEARCH CLINIC APPROACH AT UPBJJ-UT SEMARANG - Binti Muflikah; Swidarto Swidarto; Vica Ananta Kusuma (Universitas PGRI Semarang, 2021)
Scientific writing plays a crucial role in determining the quality of students and universities. So far, the ability of students to establish scientific works is varied. Some students can produce scientific work in an APIK (Asli, Penting, Ilmiah, Konsisten) way which means Original, Important, Scientific, and Consistent), as well as in a